Optimization of a rapid DNA extraction protocol in rice - Azin Fouladvand, 1987-; Muhammad Arshad Javed; Fakulti Biosains dan Kejuruteraan Perubatan (2013)
Thesis (Sarjana Sains (Bioteknologi)) - Universiti Teknologi Malaysia, 2013